2011
DOI: 10.1111/j.1349-7006.2011.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of membrane type‐1 matrix metalloproteinase‐specific activatable fluorescent probe for malignant tumor detection

Abstract: Membrane type-1 matrix metalloproteinase (MT1-MMP) is a protease that activates pro-MMP-2 and pro-MMP13, which are related to tumor malignancy. Therefore, probes that specifically image MT1-MMP would be useful for malignant tumor diagnosis. In the present study, we prepared rhodamine X-conjugated anti-MT1-MMP antibody (anti-MT1-MMP mAb-ROX) as an activatable fluorescent probe and evaluated its usefulness for MT1-MMP-specific imaging. Anti-MT1-MMP mAb-ROX was obtained in a quenched form with approximately three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…24,25) However, these optical probes were inappropriate for quantitative in vivo analysis of MT1-MMP because optical imaging suffers from photon attenuation due to absorption and dispersion as well as autofluorescence. In this regard, nuclear medical imaging would provide more accurate quantitation; therefore, several protein-based radiolabeled probes for MT1-MMP have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…24,25) However, these optical probes were inappropriate for quantitative in vivo analysis of MT1-MMP because optical imaging suffers from photon attenuation due to absorption and dispersion as well as autofluorescence. In this regard, nuclear medical imaging would provide more accurate quantitation; therefore, several protein-based radiolabeled probes for MT1-MMP have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence intensity of the probe was increased approximately 14-fold in the presence of detergent. It was confirmed that the cellular internalization of MT1-MMP activated anti-MT1-MMP mAb-ROX fluorescence, which allowed the visualization of MT1-MMP expression in C6 glioma cells [41]. However, the fluorescence wavelength of ROX (k ex = 575 nm, k em = 602 nm) was too short for in vivo optical imaging.…”
Section: Nanoprobes Realized By Specific Recognition Of Mmps With Antmentioning
confidence: 69%
“…Except for the recognition of MMPs with peptides, another approach of the ''turn-on'' fluorescent probes is realized by MMP-antibody interaction [41,42]. The self-quenching of the probe was caused by fluorophore binding to antibody and fluorescence activation was triggered on unfolding and degeneration of the fluorophore-conjugated antibody.…”
Section: Nanoprobes Realized By Specific Recognition Of Mmps With Antmentioning
confidence: 99%
“…In fact, some fluorogenic probes activated by or binding with MT1-MMP have successfully imaged tumors. (20)(21)(22) However, these probes were insufficient for quantitative analysis of MT1-MMP in vivo. In this regard, radiolabeled probes were expected to achieve more accurate quantitation; therefore, several radiolabeled probes for MT1-MMP have been developed including the 99m Tc-MT1-mAb (9) and 123 I-labelled TIMP-2.…”
Section: Discussionmentioning
confidence: 99%